LINGUISTIC EXPRESSION OF THE CONCEPT “BREAD” IN “DIVAN” BY MAKHMUD KASHGARIY (Scientific journal of the Fergana State University, 2023)
Mahmud Kashgari's "Devonu lug'otit turk" is an invaluable source of vocabulary of Turkic languages, which also explains a number of lexemes related to everyday life. These include lexemes that fall into the paradigm of food names. This article analyzes the linguistic units related to bread used in the play.